Exploratory studies of oral and fecal microbiome in healthy human aging - Zhou, Xin; Wang, Baohong; Demkowicz, Patrick C.; Johnson, Jethro S.; Chen, Yanfei; Spakowicz, Daniel J.; Zhou, Yanjiao; Dorsett, Yair; Chen, Lei; Sodergren, Erica; Kuchel, George A.; Weinstock, George M. (Frontiers in Aging, 2022)
Growing evidence has linked altered host fecal microbiome composition to health status, common chronic diseases, and institutionalization in vulnerable older adults. However, fewer studies have described microbiome changes in healthy older adults without major confounding diseases or conditions, with the impact of aging on microbiome across different body sites remaining unknown. Using 16S ribosomal RNA gene sequencing, we reconstructed the composition of oral and fecal microbiomes in young (23-32; mean=25 yrs old) and older (69-94; mean=77 yrs old) healthy community-dwelling research subjects. In both body sites, we identified changes in minor bacterial Operational Taxonomic Units (OTUs) between young and aged subjects. However, the composition of the predominant bacterial species of the healthy aged group in both microbiomes was not significantly different from that of the young cohort, suggesting that dominant bacterial species are relatively stable with healthy aging. In addition, abundance of potentially pathogenic genera, such as Rothia and Mycoplasma, was enriched in the oral microbiome of the healthy aged group relative to the young cohort. We also identified several OTUs having a prevalence above 40%, with some being more common in young and others in healthy old adults. Differences with aging varied for the oral and fecal samples, suggesting the possibility that some minor bacteria are differentially affected by aging in a tissue specific fashion. This is the first study to investigate both oral and fecal microbiomes in the context of human aging, providing new insights into interactions between aging and the microbiome within two different clinically relevant sites.